4-Hydroxyisoleucine as a Natural DPP-4 Inhibitor for Diabetes - Thalib, Amir; Damayanti, Irma Putri (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Research on 4-hydroxyisoleucine, a natural compound found in several plant sources, shows potential as an antidiabetic agent through inhibiting the DPP-4 (dipeptidyl peptidase-4) enzyme. This study evaluates the pharmacokinetic potential and toxicity profile of 4-hydroxyisoleucine as a therapeutic agent. ADME (Absorption, Distribution, Metabolism, Excretion) analysis indicates that this compound has good gastrointestinal absorption, moderate water solubility, and limited penetration across the blood-brain barrier, which reduces the risk of central nervous system side effects. The toxicity profile of 4-hydroxyisoleucine reveals low hepatotoxicity, with no indications of mutagenicity or carcinogenicity. The LD50 value greater than 2000 mg/kg places this compound in Toxicity Class 5, indicating low toxicity. Based on in silico evaluation results, 4-hydroxyisoleucine has potential as an effective natural DPP-4 inhibitor, with stable binding mechanisms, even though its binding affinity is lower thanÂ synthetic inhibitors. With favorable pharmacokinetic properties and a beneficial safety profile, 4-hydroxyisoleucine has the potential to be developed as a natural therapeutic agent for diabetes management.